Experimental investigation of the Ca-Cu process for H2 production: Evaluation of reduction/calcination strategies. (April 2019) - Díez-Martín, L.; López, J.M.; Martínez, I.; Grasa, G.; Murillo, R.; Fernández, J.R.
Highlights: A Cu/Ca molar ratio of 2 allowed achieving 95% CaCO3 calcination efficiency. The mixture sorbent/catalyst produced 94% vol. H2 at 10 bar, 650 °C and S/C = 3. SMR at 800 °C generated a gas with H2 /CO molar ratio of 3.5 and cooled the bed. The calcination/reduction and SMR reactions can be performed in a single step. Abstract: The exothermic reduction of the CuO present in a bed of solids (39% wt. CuO, 24.5% wt. CaCO3 and 1.5% wt. Ni, being the rest inert species for the process) with a fuel gas, generated a pure CO2 stream once steam was condensed (and free of N2 ). In this way, a Cu/Ca molar ratio of approximately 2 in the bed of solids allowed for CaCO3 calcination efficiencies of around 95% molar basis at the reducing gases break-through. This allowed performing consecutive cycles of the main reaction steps involved in the Ca/Cu H2 production process. The mixture CaO-based sorbent, reforming catalyst and Cu-based material was able to produce a gas stream with a 94.0% vol. H2 at 10 bar during the CH4 sorption enhanced reforming stage. The Cu-based material was oxidized with a highly diluted air stream at 10 bar, reacting in a well defined reaction front. A pure CO2 gas stream was obtained at reactor exit during the calcination/reduction stage with a fuel gas typical composition of a Steam Methane Reforming (SMR) stage with low steam to carbon molar ratio (S/C). The experimental results indicated that it was possible to cool the bed and to produce a syngas with a H2 /CO molar ratio of about 3.5 suitable for its use in the calcination/reduction stage, in a SMR stage with low (S/C). It was also possible to perform the calcination/reduction and SMR in one single stage.